Trauma Healing Anak Pasca-Banjir Di Gampong Beurawang, Pidie Jaya: Pendekatan Edukatif Dan Komunikatif - Indah Rastika Sari; Muhammad Syarif (Kalam: Jurnal Agama dan Sosial Humaniora, 2026)
Floods in Gampong Beurawang, Pidie Jaya, have caused significant psychological impacts on children, including stress, fear, and difficulties in post-disaster adaptation. This study aims to describe the implementation of trauma healing for children after floods using an educational and communicative approach. A qualitative descriptive method with a field study was employed, including observations, interviews, and documentation conducted on January 11, 2025. The findings indicate that trauma healing combining  educational  games,  group  activities,  and  empathetic communication enhances children’s emotional regulation, social participation, and self-confidence. Children were able to express feelings, collaborate, and develop social skills through positive interactions with facilitators. The educational and communicative approach also strengthened children’s coping mechanisms, supporting recovery from trauma and providing meaningful learning experiences. These results underscore the importance of a holistic trauma healing model for children in post-disaster contexts.